PREVENTION OF COMPLICATIONS WITH SPONTANEOUS BACTERIAL PERITONITIS WITH LIVER CIRRHOSIS OF VIRAL ETIOLOGY - Mukhammadieva M. I. (Web of Journals Publishing, 2024)
Spontaneous bacterial peritonitis (SBP) is defined as a bacterial infection of the ascitic fluid without a surgically treatable intra-abdominal infection source. SBP is a common, severe complication in cirrhosis patients with ascites, and if left untreated, in-hospital mortality may exceed 90%. However, the incidence of SBP has been lowered to approx. 20% through early diagnosis and antibiotic therapy. Clinical awareness, prompt diagnosis, and immediate treatment are advised when caring for these patients to reduce mortality and morbidity.
Keywords: Cirrhosis, infection, spontaneous bacterial peritonitis, multidrug-resistant bacteria, antibiotics.